Peningkatan Keterampilan Percakapan Bahasa Mandarin Tingkat Dasar Melalui Metode Picture and Picture Bagi Siswa SMA Swasta Dharma Pancasila Medan - T. Kasa Rullah Adha; Mhd. Pujiono; Intan Erwani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
Along with the times and the demands of industry 4.0, strict technological, economic, social, and cultural developments make every country compete, and everything becomes very easy to access. For this reason, building human resources that are hard-working, dynamic, skilled, and mastering science and technology is necessary to invite talents from other countries to cooperate with Indonesia. Currently, Indonesia has collaborated with other countries, one of which is China. Therefore, in this community service activity, efforts will be made to improve Mandarin's conversational skills through the picture to picture method. This activity has been carried out online through zoom meetings. The number of students who took part in this activity was 20 students of SMA Dharma Pancasila. In its implementation, the picture and picture method approach is used with materials from power points that have been optimized by the service team and specifically for high school students. This community service has resulted in the outcome, namely assistance in improving Chinese conversations, which impacts improving students' Mandarin language skills